2013
DOI: 10.2478/agms-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Probabilistic Proof of the Assouad Embedding Theorem with Bounds on the Dimension

Abstract: On redémontre de manière constructive un résultat de Naor and Neiman (à paraître, Revista Matematica Iberoamercana), qui dit que pour tout espace métrique doublant (E, d), il existe N ≥ 0, qui ne dépend que de la constante de doublement, tel que pour tout exposant α ∈]1/2, 1[, il existe une application bilipschitzienne F de (E, d α )à valeurs dans R N .Abstract. We give a constructive proof of a theorem of Naor and Neiman, (to appear, Revista Matematica Iberoamercana), which asserts that if (E, d) is a doublin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
1
6
0
1
Order By: Relevance
“…Recently, Naor and Neiman [NN12] (cf. also [DS13]) obtained estimates of N depending only on the doubling constant and independent of α, for α ∈ (1/2, 1). Note that the doubling condition is important for 2 -embeddability in Theorem 3.9.…”
Section: Weighted Diamonds Are Bilipschitz-equivalent To Snowflaked Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Naor and Neiman [NN12] (cf. also [DS13]) obtained estimates of N depending only on the doubling constant and independent of α, for α ∈ (1/2, 1). Note that the doubling condition is important for 2 -embeddability in Theorem 3.9.…”
Section: Weighted Diamonds Are Bilipschitz-equivalent To Snowflaked Dmentioning
confidence: 99%
“…One of the most important results on this problem is the Assouad theorem, which we mention below (Theorem 3.9). However, it should be mentioned that in the present context we are interested in the version of the problem for which the dimension is specified, see very interesting recent results related to this problem in [NN12,DS13], and related comments in [Hei03, Remark 3.16].…”
Section: Low-dimensional Euclidean Subsetsmentioning
confidence: 99%
“…Characterizing the quantitative dependence in terms of geometric properties of the target norm on R k has not been carried out yet (it isn't even clear what should the pertinent geometric properties be), though see [114] for an almost isometric version when one considers the ∞ norm on R k (with the dimension k tending to ∞ as the distortion approaches 1); see also [103] for a further partial step in this direction. In [191] it was shown that for θ ∈ [ 1 2 , 1) one could take k(K, θ) k(K) to be bounded by a constant that depends only on K; the proof of this fact in [191] relies on a probabilistic construction, but in [77] a clever and instructive deterministic proof of this phenomenon was found (though, yielding asymptotically worse estimates on α(K, θ), k(K) than those of [191]).…”
Section: Infinite Subsets Of Hilbert Spacementioning
confidence: 99%
“…6 On its own, the established necessity of obtaining a genuinely nonlinear embedding method into low dimensions should not discourage attempts to answer Question 41, because some rigorous nonlinear dimension reduction methods have been devised in the literature; see e.g. [24,233,63,110,32,33,139,146,59,154,62,1,34,112,191,77,150,203,103,30,201,206,16]. However, all of these approaches seem far from addressing Question 41.…”
Section: Infinite Subsets Of Hilbert Spacementioning
confidence: 99%
“…A metric space quasisymmetrically embeds into some Euclidean spaces if and only if it is doubling (see [Hei01,Theorem 12.1]). More specifically, Assouad proved the following result (see [Ass83], and also [NN12,DS13]): if (X, d) is a doubling metric space and α ∈ (0, 1) then the metric space (X, d α ) admits a bi-Lipschitz embedding into some Euclidean space. If d E is the Euclidean distance and α = log 2/ log 3 then the metric space ([0, 1], d α E ) is bi-Lipschitz equivalent to the von Koch snowflake curve, so (X, d α ) is said to be the α-snowflake of (X, d).…”
Section: Introductionmentioning
confidence: 99%